Assessing ozone and nitrogen impact on net primary productivity with a Generalised non-Linear Model. - De Marco, Alessandra; Screpanti, Augusto; Attorre, Fabio; Proietti, Chiara; Vitale, Marcello (Environmental pollution (Barking, Essex : 1987), 2013)
Some studies suggest that in Europe the majority of forest growth increment can be accounted for N deposition and very little by elevated CO(2). High ozone (O(3)) concentrations cause reductions in carbon fixation in native plants by offsetting the effects of elevated CO(2) or N deposition. The cause-effect relationships between primary productivity (NPP) of Quercus cerris, Q. ilex and Fagus sylvatica plant species and climate and pollutants (O(3) and N deposition) in Italy have been investigated by application of Generalised Linear/non-Linear regression model (GLZ model). The GLZ model highlighted: i) cumulative O(3) concentration-based indicator (AOT40F) did not significantly affect NPP; ii) a differential action of oxidised and reduced nitrogen depositions to NPP was linked to the geographical location; iii) the species-specific variation of NPP caused by combination of pollutants and climatic variables could be a potentially important drive-factor for the plant species' shift as response to the future climate change.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23078996
Keywords: Generalized Linear/non-Linear Model; Mediterranean climate; Net primary productivity; Nitrogen deposition; Ozone